ANALISIS PENGARUH GAYA TERHADAP FATIGUE LIFE BAJA STRUKTURAL PADA PEGAS DAUN MENGGUNAKAN ANALISIS ELEMEN HINGGA - Kusmiran, Amirin; Said L, Muh. (JFT : Jurnal Fisika dan Terapannya, 2019)
Leaf spring is one of a component of the vehicle which are used to vibration damping caused by the force. Some cases that occur in the vehicle namely overload. This case can affect to fatigue life of steel leaf spring. One of a method that use to fatigue life prediction is high fatigue cycle where this method can be simulated using the finite element method. The number both element and node used in this research where 6961 element and 14726 nodes, respectively. Magnitude of the force used is 80 KN, 100 KN, and 200 KN where thus force are used to prediction of the fatigue life steel leaf spring. The result of this research revealed force 80 KN have the fatigue life longer than force 200 KN and 200 KN which is 106 cycle. In addition, the critical value of the fatigue life 80 KN is smaller than 100 KN, and 200 KN. As such as, the force 80 KN is recommendation as allowed force which use to vehicle. This value is validated by safety factor analysis where the force allowed as 80 KN with safety factor equal to 2.56.